Proportion, quality of life and factors associated with perinatal urinary incontinence among pregnant women attending at Muhimbili national hospital - Geofrey P. Chiloleti; Fransia Arda Mushi; Aboud Muhsin; Ally Mwanga (African Journal of Urology)
Abstract Background Perinatal urine incontinence (PUI) affects approximately 200 million women worldwide. It is hypothesized that it has a multifactorial etiology that includes hormonal changes, pregnancy, urethral angle changes, and childbirth-related forces. The prevalence of PUI ranges from 32 to 64%. These conditions affect quality of life, leading to significant physical and emotional distress, self-esteem, social interactions, postpartum depression and anxiety. Determining the factors associated with PUI and providing appropriate support and treatment options for women experiencing perinatal urinary incontinence can improve the well-being of those affected. The significance of this study is to help establish the foundation of Perinatal urinary incontinence awareness in our facility, and possibly knowing the burden and associated risk factors, care to be taken in the reassurance of the patient and, for a future urological approach and overall management. Objectives To assess the proportion, quality of life and factors associated with perinatal urinary incontinence among pregnant women admitted to the Muhimbili national hospital. Methodology This prospective cross-sectional study involved 354 pregnant women in perinatal period. The statistical analysis of the data was done in the SPSS version 20, whereby descriptive statistics and categorical data were described by frequency tables, graphs, and percentages, and numerical variables by mean, median, and standard deviation. Bivariate logistic regression was used to obtain variables that were associated with PUI. Multivariate logistic regression for controlling for confounders. P value of < 0.5 was considered to be statistically significant. Quality of life (QoL) was assessed by ICIQ-UI SF tool. Results A total of 354 women were approached, all of whom participated in the study. The mean age of the participants was 30 years (range 30–34 years). The overall proportion of PUI among the participants was 59 [16.7%]. Of the total participants with PUI, 28 (49.1%) had Stress urine incontinence (SUI), 9 (15.8%) had Urge urine incontinence (UUI), Mixed urine incontinence (MUI), and 1 (1.8%). Overall, among the participants who had PUI, quality of life (QoL) was moderately affected in 31 (52.5%) participants, followed by 17 (28.8%) whose QoL was slightly affected, 10 (16.9%) whose QoL was poor, and only 1 (1.7%) whose quality of life was very poor. In the multivariable logistic regression model, Factors associated with PUI were statically significant, with P < 0.05. A significant association between UI and a normal BMI, pre-obesity [AOR 1.351 95% CI 1.161–1.765], grand multipara [AOR 1.092 95% CI 1.027–1.323], and a previous history of cesarean section [AOR. 5.126 95% CI 2.081–12.628]. Conclusions Perinatal urinary incontinence has a considerable impact on health complications across various aspects, despite not being a life-threatening condition. The effects of urinary incontinence extend to daily activities, sexual health, personal relationships, social engagement, and mental well-being.